1988
DOI: 10.1139/v88-465
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the binding step in dopamine receptor–antagonist interactions

Abstract: Modelling of the binding step in dopamine receptor–antagonist interactions was undertaken using sixteen antagonists belonging to the following five chemical series: phenothiazines, thioxanthenes, butyrophenones, benzamides, and benzisoxazoles. The Lower Unoccupied Molecular Orbitals (LUMOs) of the antagonists used for these interactions were compared using a similarity τij index, which enabled us to define the characteristic orbital forms of the active molecules. The result of the intersection of these represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…The interaction of frontier orbitals (HOMO, highest occupied molecular orbital and LUMO, lowest unoccupied molecular orbital) has been shown to play a role in chemical reactivity (Chan et al, 2007a;Osman et al, 1988). Generally, HOMO of the nucleophile reacts with the LUMO of the electrophilic species (Lewis, 1999), where LUMO typically acts as an electron acceptor in chargetransfer interactions (Boudon et al, 1988). Previous work from our laboratory showed that E LUMO was also a good descriptor for hepatotoxic effects for a series of pbenzoquinones which are also electrophilic compounds that act via Michael-type mechanism (Chan et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%
“…The interaction of frontier orbitals (HOMO, highest occupied molecular orbital and LUMO, lowest unoccupied molecular orbital) has been shown to play a role in chemical reactivity (Chan et al, 2007a;Osman et al, 1988). Generally, HOMO of the nucleophile reacts with the LUMO of the electrophilic species (Lewis, 1999), where LUMO typically acts as an electron acceptor in chargetransfer interactions (Boudon et al, 1988). Previous work from our laboratory showed that E LUMO was also a good descriptor for hepatotoxic effects for a series of pbenzoquinones which are also electrophilic compounds that act via Michael-type mechanism (Chan et al, 2007a).…”
Section: Discussionmentioning
confidence: 99%